Study the early complications of modified radical mastectomy performed - Chandrakar, Naman; Shinde, Raju K. (International Surgery Journal, 2018)
Background: According to the national and regional cancer registries, breast cancer is the most common cancer among women in Delhi, Mumbai, Kolkata, Ahmadabad and Thiruvananthapuram. Methods: The present Prospective and observational study was conducted in the Department of Surgery of Acharya Vinoba Bhave Rural Hospital attached to Jawaharlal Nehru Medical College. Forty-one patients of carcinoma breast were treated with modified radical mastectomy from September 2013 to September 2015. Results: The mean age of cases was 50.90 years with a standard deviation of 11.61 years. only 1 male patient (2.44%) was diagnosed with carcinoma breast and 40 female patients (97.56%) out of 41 total cases. In all the 41 cases (100%) chief complaint was lump in breast, followed by axillary swelling in 11 cases (26.83%) and history of pain (in lump) in 8 cases (19.51%). ecchymosis of the flap was seen in 8 patients (19.51%). The 10 cases (24.39) had surgical site infection, Minimal seroma collection (<10ml) was seen in 9 cases. 3 cases (7.32%) had pain at the surgical site. Tissue necrosis was observed in 7 cases (17.07%). Conclusions: It was concluded that Post-operative complications of MRM included wound dehiscence, seroma, surgical site infection, hematoma, altered sensation and pain.